PENGARUH LATIHAN ISOMETRIK BERBENTUK STANDING PULL-UP TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA SISWA PUTRA EKSTRAKURIKULER BULUTANGKIS SMK N 4 PEKANBARU - Kuanawaty '; Slamet '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This research was conducted to find out whether there is influence effects of exercise on the standing pull-up about strength muscle bracialis and humeri at student exstracurricular badminton so that when doing a smash to get maximum results.This research is a from of research with experimental treatment (Experimental), with population of students extracurriculer badminton SMKN 4 Pekanbaru, in this study all population data of 10 poeple. The instruments used in this research is insteresting expanding Dynamometer test, which aims to measure the strength muscle bracialis and humeri. After that, data is processed whith statistics, to the test normality of the test atb significant  level 0,05a lilifors. Hypotesis proposed, excercise effect of Standing Pull-Up about Strength Muscle Bracialis and Humeri.Based on the analysis produces 6,36 Thitung and 1,833 Ttabel, its means Thitung>Ttabel. Based on the analysis of statistical data, there are one Pree-test average was 19,6 and Post-test average 21, data is normal. Then, there is a Exercise Effect of  Standing Pull-Up about Strength Muscle Bracialis and Humeri at Students Extracurriculer Badminton SMKN 4 Pekanbaru. Keywords: Isometric, Standing Pull-Up, Strength  Muscle Bracialis and Humeri